Tindak Pidana “Obstruction of Justice” dalam Pengaturan Undang-undang Nomor 1 Tahun 2023 - Ismail Pettanasse; Febrina Hertika Rani; M. Adi Saputra; Dea Justicia Ardha (CV. Doki Course and Training, 2024)
Law enforcement efforts must pay attention to the criminal offence of Obstruction of Justice, because it can have an impact on the law enforcement process itself. Thus, this research discusses how the regulation of the criminal offence of Obstruction of Justice in the legislation. The purpose of this research is to understand what actions are included in the category of Obstruction of Justiice. The type of research used is normative legal research. The research data used is secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The results of the study suggest that in Law Number 1 Year 2023, the criminal offence of Obstruction of Justice is regulated in more detail in Chapter VI on Criminal Offences Against the Judicial Process, which is divided into three parts: Misdirection of the Judicial Process: Includes falsification of evidence, giving false testimony, and actions that interfere with the judicial process. The maximum sanction is six years imprisonment or a category V fine (Article 278), Disrupting and Obstructing the Judicial Process: Includes disrupting a trial, disobeying a court order, attacking the integrity of the authorities, and obstructing an investigation. The maximum sanction is seven years and six months' imprisonment or a category IV fine. (Articles 279-292), Destruction of Court Buildings, Courtrooms, and Court Equipment: This includes damaging the court building or court equipment which results in the court session not being able to continue. The maximum sanction is five years imprisonment. (Article 293) In addition, Law No. 1 of 2023 also covers the Protection of Witnesses and Victims from Article 294 to Article 299, to ensure safety and justice for witnesses and victims in the judicial process.